2009
DOI: 10.1111/j.1478-3231.2010.02280.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype diversity of hepatitis C virus (HCV) in HCV-associated liver disease patients in Indonesia

Abstract: Hepatitis C virus core sequence (237 bases) could identify the HCV subtype and the prevalence of HCV subtype based on core sequence was similar to those based on the NS5B region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…HCV-2a was previously reported as the most common (52z) among the HCV clones obtained from blood donors in Indonesia, followed by HCV-1b (15z), HCV-1a (7z), and HCV-1c (7z), which is a unique Indonesian subtype (22). In a more recent study of patients with chronic liver disease, Utama et al reported that HCV 1b (47.3z) was the most prevalent subtype, followed by 1c (18.7z), 3k (10.7z), 2a (10.0z), 1a (6.7z), 2e (5.3z), 2f (0.7z), and 3a (0.7z) (37). Among people with HCV-HIV co-infection in Surabaya, those who were positive for anti-HCV antibodies showed HCV-1a (31.5z) as the predominant subtype, followed by 3a (23.3z), 1c (10.9z), 1b (9.6z), 3k (4.1z), 2a (1.4z), 4a (1.4z), and genotype 1 (16.4z) (19).…”
mentioning
confidence: 99%
“…HCV-2a was previously reported as the most common (52z) among the HCV clones obtained from blood donors in Indonesia, followed by HCV-1b (15z), HCV-1a (7z), and HCV-1c (7z), which is a unique Indonesian subtype (22). In a more recent study of patients with chronic liver disease, Utama et al reported that HCV 1b (47.3z) was the most prevalent subtype, followed by 1c (18.7z), 3k (10.7z), 2a (10.0z), 1a (6.7z), 2e (5.3z), 2f (0.7z), and 3a (0.7z) (37). Among people with HCV-HIV co-infection in Surabaya, those who were positive for anti-HCV antibodies showed HCV-1a (31.5z) as the predominant subtype, followed by 3a (23.3z), 1c (10.9z), 1b (9.6z), 3k (4.1z), 2a (1.4z), 4a (1.4z), and genotype 1 (16.4z) (19).…”
mentioning
confidence: 99%
“…HCV-2 exhibits high genetic diversity in West Africa, where it has thought to have endemically persisted and spread for at least 500 years (20). In addition, isolated pockets of endemic HCV-2 transmission have been found in geographic regions out-side Africa, including the Caribbean (21,39), Indonesia (41), and Vietnam (26). These lineages fall within the greater African diversity, but the extent of their divergence suggests dissemination from Africa before the rise of global travel and modern medicine (20).…”
mentioning
confidence: 99%
“…In the case of HCV2c, the ID had 3033 AA protein sequences (27) . The HCV2d, the ID contained 149 AA protein sequences (34) .The HCV2e study allowed us to obtain ID of 119 AA protein sequences (33) . In the case of HCV2f, the ID had 93 AA protein sequences (33) .…”
Section: Exposed Protein Databases Hcv Genotypesmentioning
confidence: 99%